Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction

Surface chemical bonds, surface-enhanced Raman scattering, and dielectric constant of SiO2 nanospheres in-situ decorated with Ag-nanoparticles by electron-irradiation - Phatangare, A. B.; Dhole, S. D.; Dahiwale, S. S.; Mathe, V. L.; Bhoraskar, S. V.; Late, Dattatray J.; Bhoraskar, V. N. (Journal of Applied Physics, 2016)
Nanostructures of dielectric materials decorated with metal nanoparticles are of great scientific interest; however, the involved synthesis methods are complicated and require multistep chemical processing, including functionalization of the dielectric surfaces. In the present work, without chemical processes, silver nanoparticles of average sizes in the range of 11 to 15 nm were in-situ synthesized and decorated on SiO2 nanospheres in a single step process by irradiating a solution (AgNO3-polyvinylpyrrolidone (PVP)-SiO2 nanospheres) with 6 MeV electrons at 1.5 x 10(15) e(-)/cm(2), 3.0 x 10(15) e(-)/cm(2), and 4.5 x 10(15) e(-)/cm(2) fluences. The electron irradiated solutions were characterized with different surface and other techniques. The results revealed that the SiO2 nanospheres were uniformly decorated with Ag nanoparticles, and the prominent chemical bonds involved were Ag-O, Si-O-Ag, and Si-Ag. Moreover, the sizes and the decoration density of Ag nanoparticles could be tailored by varying electron fluence. The Surface-enhanced Raman scattering (SERS) of 4-aminothiophenol (4-ATP) solutions was studied using substrates in the form of thin coatings of the solutions of Ag-decorated SiO2 nanospheres. The appearance of the characteristic SERS peaks of both 4-ATP and 4, 4'-dimercaptoazobenzene (4, 4'-DMAB) in Raman spectra confirmed the conversion of a fraction of 4-ATP into 4, 4'-DMAB in the presence of Ag nanoparticles. Composites in the form of thin films were synthesized from the mixture solutions of PVP and Ag-decorated SiO2 nanospheres. The dielectric constant of each thin film was higher as compared to polymers, and could be tailored by varying electron fluence used for decorating Ag nanoparticles. Published by AIP Publishing.

Effects of gamma irradiation on non-polar GaN films deposited on sapphire using pulsed laser deposition - Rajgoli, Tahir; Sant, Tushar; Jejurikar, Suhas M.; Hinge, Sandip; Banpurkar, Arun; Dahiwale, S. S.; Late, Datta (Applied Surface Science, 2024)
The GaN films/layers exposed to gamma-radiations is known to harvest defects and vacancies in the crystals producing donor, acceptor and recombination centers within the bandgap. Therefore it is important to investigate and study the gamma- ray irradiation effects on various physical and chemical properties of a material before any optoelectronic and/or electronic devices are being fabricated. To avoid Stark effect which is observed in most of the optoelectronic devices fabricated using GaN films grew along polar face, use of non-polar GaN films is suggested by researchers. To address such issues the article reports the investigations of physical and chemical properties of non-polar GaN films grown on polar substrate using pulsed laser deposition, which were exposed to the 60Co gamma rays varying dose values. Resistive nature against the impairment of the films caused by gamma-rays observed herewith is highly encouraging, suggesting the use of non-polar GaN films as radiations harden material suitable for fabricating new generation gamma-ray detectors. To our knowledge very limited information is available that report such investigations.
Keywords: Gallium nitride; Gamma rays; PL emission; pulsed laser deposition